Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy (CADASIL). Issue 1 (1st February 2004) - Razvi, S. Saif M.; Muir, Keith W.
Abstract : INTRODUCTION Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited, autosomal dominant condition with high penetrance and varying expression. It is an important cause of protracted disability in young adults, with recurrent strokes, psychiatric dysfunction, and dementia. Although some families were identified in the 1950s, the syndrome was characterized and named only in 1993. The prevalence remains unknown, but numbers are increasing in parallel with wider medical recognition. GENETICS, PATHOLOGY AND PATHOPHYSIOLOGY CADASIL is caused by mutations in the Notch3 gene (chromosome 19p13) (Joutel et al . 1996), which encodes a large single-pass transmembrane receptor. The receptor's extracellular domain contains 34 epidermal growth factor-like tandem repeats (EGF repeats). This receptor is part of a highly conserved signalling pathway that is essential for normal maturation of blood vessels in both fetal and adult brain, and is maximally expressed in small to medium penetrating arteries in early postnatal development